THE IMPLEMENTATION OF THE LONG-TERM CONTRACEPTIVE METHOD FAMILY PLANNING PROGRAM IN CANGKERING VILLAGE, AMUNTAI SELATAN SUB-DISTRICT, HULU SUNGAI UTARA REGENCY - M. Ridha Anshari; Haji Mukti Ramadhani; Noor Jannah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The Family Planning Program using Long-Term Contraceptive Methods (MKJP) is one of the government’s efforts to control population growth and improve reproductive health quality. However, various problems remain in its implementation, particularly the low utilization of MKJP in Cangkering Village, Amuntai Selatan District, Hulu Sungai Utara Regency. These problems are caused by limited socialization and information, fears and myths regarding side effects, lack of support from husbands and families, as well as social and religious views that consider MKJP to be contrary to religious teachings. This study aims to examine the implementation of the MKJP Family Planning Program in Cangkering Village and the factors influencing it. This study employed a descriptive qualitative research method. Data were collected through observation, interviews, and documentation. A total of 11 informants were selected using purposive sampling techniques. Data analysis was conducted through data collection, data condensation, data display, and conclusion drawing and verification.The results indicate that the implementation of the MKJP Family Planning Program in Cangkering Village is categorized as fairly good. Well-implemented aspects include control over funding sources, leadership support, and the quality of leadership within the relevant institutions. Moderately well-implemented aspects include adequate facilities, clarity and consistency of targets, technical skills of officers, internal communication, and inter-agency relationships with target groups. Meanwhile, poorly implemented aspects include limited human resources, socio-cultural influences, low involvement of program beneficiaries, weak effectiveness of support networks, and limited commitment of officers to the program. Supporting factors consist of the availability of funds and leadership motivation, while inhibiting factors include insufficient socialization, lack of support from husbands and families, and cultural influences on the acceptance of MKJP within the community.